Dr. Diyana creates Hear Me app to assist students with special needs - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 5 July 2021 - For more than a year, the country has been facing the Covid-19 pandemic. Since then, a new norm learning environment has been established to implement home-based teaching and learning (PdPR) for students, including those with special needs.